PTX-loaded, polysorbate 80-functionalized brain-targeting pullulan nanoparticles for drug delivery - Yuan, Huabing; Han, Lu; Deng, Hao; Tan, Yue; Yang, Yi; Liu, Yi; Ying, Jiaxin; Fang, Mengqi; Wei, Hui; Tao, Zhihe (Frontiers in Pharmacology, 2026)
Brain-targeted drug delivery remains a major challenge in pharmaceutical research. In this study, four types of polysorbate 80 and cholesterol-modified pullulan polymers (CHPP) were synthesized and self-assembled into nanoparticles (CHPP NPs) for brain drug delivery. The properties of these NPs, including brain targeting efficiency, were systematically evaluated to investigate the influence of polymer modification on their performance. The hydrophobicity of the polymers increased with the degree of cholesterol substitution, which in turn led to a reduction in nanoparticle size. Furthermore, higher hydrophobicity contributed to an increased drug loading capacity for paclitaxel (PTX) and a more sustained drug release profile. In vivo fluorescence imaging revealed that formulations with higher levels of polysorbate 80 and cholesterol modification exhibited significantly enhanced brain targeting efficiency compared to other variants. The PTX-loaded CHPP NPs (PTX-CHPP NPs) demonstrated potent cytotoxicity and inhibitory effects against SJ-GBM2 glioma cells in vitro, underscoring their potential as a promising platform for brain-targeted drug delivery. These findings provide valuable insights for the rational design of brain-targeting nanocarriers.